Peningkatan Kemampuan Bahasa Ekspresif Anak melalui Metode Bercerita dengan Media Gambar Berseri di TK Aprillya - Siti Mauliza; Yuhasriati Yuhasriati; Rahmi Sofyan (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study was motivated by the low expressive language skills of 4-5 year old children at Aprillya Aceh Besar Kindergarten, particularly in their ability to retell stories they have heard, which does not meet the indicators of the Child Development Achievement Standards (STPPA). The purpose of this study was to improve children's language skills through the application of storytelling methods using serial images. The language skills referred to in this study are expressive language skills, namely the ability of children to retell stories they have heard. The method used in this study was the Kurt Lewin model of Classroom Action Research (CAR) with 7 children aged 4–5 years in group A at Aprillya Aceh Besar Kindergarten as the research subjects. Data collection techniques were carried out through observation of teacher activities and children's language skills, using observation sheets as instruments. The results of the study can be concluded that improving children's language skills can be done through the following steps: teachers prepare a series of pictures, teachers create an orderly, calm, and conducive learning atmosphere, teachers introducing children to a series of pictures about landslides, teachers asking children to pay attention to the pictures while teachers narrate the pictures, teachers pausing the story for a moment and asking questions to children, teachers asking children to retell the story from the series of pictures that have been read by teachers. This can be seen from the improvement in children's development, where at the end of cycle II, 6 children reached the category of Developing as Expected (BSH)